Bacterial extracellular vesicles and associated functional proteins in fermented dairy products with Lacticaseibacillus paracasei - Pérez Martínez, Gaspar; Giner-Pérez, Lola; Castillo-Romero, Keshia F. (Frontiers in Microbiology, 2023)
and body fluids. Lacticaseibacillus paracasei produces EV that have attached biologically active proteins (P40 and P75). In this work found EV and functional proteins were found in five different commercial dairy fermented products carrying L. paracasei. Strains present in those products were isolated and, with one exception, all produced small EV (24-47 d.nm) carrying P40 and P75. In order to winnow bacterial EV from milk EV, products were subject to centrifugal fractionation at 15,000 xg (15K), 33,000 xg (33K) and 100,000 xg (100K). P75 was present in all supernatants and pellets, but P40 was only found in two products bound to the 15K and 33K pellets, and 16S rDNA of L. paracasei could be amplified from all 100K EV, indicating the presence of L. paracasei EV. To investigate the interactions of bacterial EV and proteins with milk EV, L. paracasei BL23 EV were added to three commercial UHT milks. Small size vesicles (50-60 d.nm) similar to L. paracasei BL23 EV were found in samples from 100K centrifugations, but intriguingly P40 and P75 were bound to EV in 15K and 33K pellets, containing bovine milk EV of larger size (200-300 d.nm). Sequencing 16S rDNA bands amplified from EV evidenced the presence bacterial EV of diverse origin in milk and fermented products. Further, L. paracasei 16S rDNA could be amplified with species specific primers from all samples, showing the presence of L. paracasei EV in all EV fractions (15K, 33K and 100K), suggesting that this bacterial EV possibly aggregate and are co-isolated with EV from milk. While P40 and P75 proteins would be interacting with specific populations of milk EV (15K, 33K), because they were detected bound to them in fermented products and milk, and this possibly forced the sedimentation of part of L. paracasei EV at lower centrifugal forces. This pioneering work has solved technically complex problems and essential questions that will facilitate new research focusing on the molecular behaviour of probiotics during fermentations and the mechanisms of action mediating health benefits of fermented products.